Ukrainian National Values and their Forming by Usage of Educational Means, under the Conditions of Ukrainian Abroad - Stanislav Ponomarevs’kyi (Pedagogical Discourse, 2012)
The peculiarity of the modern system of Ukrainian national values, formed abroad, is analyzed in the article.